RODA: a service-oriented repository to preserve authentic digital objects - Faria, Luís (2009)
In mid 2006, the Portuguese National Archives (Directorate-General of the Portuguese Archives) launched a project called RODA (Repository of Authentic Digital Objects) aiming at identifying and bringing together all the necessary technology, human resources and political support to carry out long-term preservation of digital materials being produced by the Portuguese public administration. As part of the original goals of RODA was the development of a digital repository capable of ingesting, managing and providing access to the various types of digital objects produced by national public institutions. The development of such repository should be supported by open-source technologies and, as much as possible, be based on existing standards such as the OAIS [1], METS [2, 3], EAD [4] and PREMIS [5]. Since RODA is nearly finished, this communication aims at describing its main results.